A novel corner-fired boiler system of improved efficiency and coal flexibility and reduced NOx emissions. (15th March 2019) - Ma, Lun; Fang, Qingyan; Yin, Chungen; Wang, Huajian; Zhang, Cheng; Chen, Gang
Highlights: A novel combustion system developed to improve performance of corner-fired boilers. With optimized feeding of secondary air and vent gas out of pulverization system. Greater fuel flexibility from semianthracite to high-volatile bituminous coals. NOx reduction by over 60%; boiler efficiency increase from <92% to ca. 94%. Successfully demonstrated in retrofit of three corner-fired utility boilers. Abstract: To assure stable ignition and combustion of low-volatile coals in conventionally configured boilers, storage systems are commonly used to separate the ground coal from the air or gas and evaporated moisture prior to the combustion process, and the stored ground coal is then transported by hot air to the combustion process. This study is to develop a novel combustion system, in order to facilitate the firing of different types of coals in existing conventional corner-fired boilers originally configured for low-volatile semianthracite-firing and to improve the boiler performance. Numerical simulation, boiler retrofit and full-scale performance test are conducted. After successful demonstration in a 330 MWe semianthracite corner-fired utility boiler, the novel combustion scheme is implemented in retrofit of two other similar boilers. The simulation and full-scale performance test on all the three boilers show that the use of the new combustion system achieves a significant reduction in NOx emissions and a remarkable increase in boiler efficiency whereas induces no side effect in operation. After retrofit, these boilers can also readily accommodate low-volatile semianthracite (the design coal) and high-volatile bituminous coal (the retrofit coal), largely improving the coal flexibility.